Factors associated with different forms of alcohol use behaviors among college students in Bhutan: a cross-sectional study - Tandin Dorji; Peeradone Srichan; Tawatchai Apidechkul; Rachanee Sunsern; Wipob Suttana (BMC, 2020)
Abstract Background Alcohol use has impacts on several dimensions of health, including physical health and mental health, particularly in college-age populations. Therefore, this study aimed to estimate the prevalence and to determine factors associated with alcohol use behaviors among college students in Bhutan. Methods A cross-sectional design was applied to collect data from the participants. A simple random method was used to select the participants from the lists of students who were attending the four selected colleges in Bhutan in the academic year of 2019. A questionnaire was developed, and validity and reliability were verified before use. Descriptive statistics were applied to describe the general characteristics of participants, while logistic regression was used to detect the associations between variables at the significance level of α = 0.05. Results A total of 432 college students were recruited into the study, of whom 62.0% were females. The average age was 20.0 years, 40.7% were the third-year students, and 79.9% lived in college dormitories. The prevalence of current drinking was 51.6% and that of binge drinking was 19.4%. After controlling for all potential confounder factors, three variables were found to be associated with current drinking: students who had low income were more likely to be current drinkers than those who had high income (AOR = 2.59, 95% CI = 1.29-5.21); students who did not use tobacco were more likely to be current drinkers than those students who used tobacco (AOR = 6.99, 95% CI = 2.90-16.81); and students who had close friends who did not use alcohol were more likely to be current drinkers than those who had close friends who used alcohol (AOR = 5.14, 95% CI = 3.04-8.69). Four factors were found to be associated with binge drinking after controlling for all possible confounder factors: students who had high income were more likely to be binge drinkers than those who had low income (AOR = 3.03, 95% CI = 1.72-5.31); students who used tobacco were more likely to be binge drinkers than those students who did not use tobacco (AOR = 2.28, 95% CI = 1.35-3.87); students whose parents used alcohol were more likely to be binge drinkers than those students whose parents did not use alcohol (AOR = 1.75, 95% CI = 1.02-3.01); and students whose close friends used alcohol were more likely to be binge drinkers than those who had close friends who did not use alcohol (AOR = 2.26, 95% CI = 1.05-4.87). Conclusions There is a high prevalence in alcohol use among the college students in Bhutan. Effective health promotion programs should be implemented by focusing on reducing the alcohol consumption among college students.